Novel nonthermal and thermal pretreatments for enhancing drying performance and improving quality of fruits and vegetables. (June 2021) - Bassey, Edidiong Joseph; Cheng, Jun-Hu; Sun, Da-Wen
Abstract: Background: Fruits and vegetables are an essential class of food with enormous nutritional and commercial gains. With the surge in interest for nutraceuticals, the demand for high-quality fruits and vegetables have gained traction in recent times. In a bid to extend shelf life and retain quality to meet demand, drying of fruits and vegetables has been accompanied by pretreatments. Conventional pretreatments have shown to improve the drying process in terms of drying kinetics and final product quality. However, for further improving and enhancing the drying process, novel nonthermal and thermal pretreatments have been investigated. Scope and approach: This paper reviews some novel nonthermal and thermal pretreatment techniques with a focus on their efficacies to improve the drying process in terms of amelioration of drying kinetics and enhancement of the functional and nutritional quality of the dried product. Details of the pretreatment techniques including cold plasma, pulsed electric field, edible coating, ultrasonication, high humidity hot air impingement blanching, infrared blanching, and microwave blanching are discussed, and their possible application drawbacks and prospects in future developments are also presented. Key Findings and Conclusions: The development and application of novel pretreatment techniques can not only shorten drying time, increase drying rate, improve moisture distribution, and lower energy consumption but can also further enhance the functional and nutritional quality attributes of the dried products better than conventionally pretreated and untreated samples. Additionally, combinations of these technologies and adequate modelling approaches for optimizing the pretreatment conditions can further boost their effectiveness in enhancing the drying process. Highlights: Pretreatments can enhance drying performance and improve product quality. Nonthermal techniques can facilitate permeability by tissue modification. Novel thermal techniques can accelerate moisture evaporation and transfer. Future work can focus on hurdle technology and process modelling.